The Impact of Writing About Gratitude on the Intention to Engage in Prosocial Behaviors During the COVID-19 Outbreak - Oliveira, Raquel; Baldé, Aíssa; Madeira, Marta; Ribeiro, Teresa; Arriaga, Patrícia (Frontiers in Psychology, 2021)
The ongoing COVID-19 pandemic has quickly swept the globe leaving a devastating trail of lost human lives and leading to a public health and economic crisis. With this in mind, prosociality has been heralded as potential important factor to overcome the negative effects of the pandemic. As such, in this study, we examined the effectiveness of a brief reflexive writing exercise about recent experiences of gratitude on individuals' intentions to engage in prosocial behaviors using a sample of 253 participants living in Portugal and 280 participants living in Brazil. Participants were randomly assigned to either a condition in which they were asked to write about recent experiences of gratitude, or a control group in which they were asked to write about daily tasks. We predicted that the gratitude intervention would increase state gratitude, and consequently, increase positive affect and empathic concern, and decrease negative affect, leading to increased intentions to engage in prosocial behaviors during the COVID-19 pandemic. A moderated serial-parallel mediation analysis, in which we controlled for gender, age, and level of religiosity, indicated that our manipulation led to increases in state gratitude, which in turn increased positive emotions and empathic concern, leading to increased prosocial intentions in both countries. A content analysis of participants’ responses in the gratitude group revealed that relationships with others and health and well-being were the central themes of their gratitude experiences during the COVID-19 global pandemic.